2022
DOI: 10.1007/s40195-022-01377-8
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Corrosion Properties of Duplex-Structured Extruded Mg-6Li-4Zn-xMn Alloys

Abstract: The extruded Mg-6Li-4Zn-xMn (x = 0, 0.4, 0.8, 1.2 wt%) alloys were prepared, and the microstructure of the test alloys was investigated by optical microscopy, scanning electron microscopy and transmission electron microscopy. The corrosion properties were determined by electrochemical measurements and immersion measurements in 3.5% NaCl solution. The results indicate that the extruded Mg-6Li-4Zn-xMn alloys are mainly composed of α-Mg phase, β-Li phase, Mn precipitates and some intermetallic compounds (MgLi 2 Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 51 publications
(53 reference statements)
0
6
0
Order By: Relevance
“…3.2, this may explain aforementioned the texture result in Fig. 8, which non-basal slips activates more frequently, especially, pyramidal < c + a > slip, providing 5 independent slip directions, including c dislocation that can coordinate deformation with a dislocation, which not only make the grain size decrease, but also trigger CDRX and DDRX to enhance the anisotropy of microsturcture [9,22]. Furthermore, all SF distributions of 4 passes extend in two opposite directions in TD.…”
Section: Texture Characterizationmentioning
confidence: 91%
See 3 more Smart Citations
“…3.2, this may explain aforementioned the texture result in Fig. 8, which non-basal slips activates more frequently, especially, pyramidal < c + a > slip, providing 5 independent slip directions, including c dislocation that can coordinate deformation with a dislocation, which not only make the grain size decrease, but also trigger CDRX and DDRX to enhance the anisotropy of microsturcture [9,22]. Furthermore, all SF distributions of 4 passes extend in two opposite directions in TD.…”
Section: Texture Characterizationmentioning
confidence: 91%
“…These LAGBs could become HAGBs with increased strain, eventually converting substructured grains into brandnew DRXed grains. A typical continuous dynamic recrystallization (CDRX) mechanism is like these [9,20,41].…”
Section: Microstructurementioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, it can be concluded that the corrosion behavior of Mg alloys in NaCl solutions depends on the Cl − concentration and the microstructural characteristics. For Mg-Li based alloys, although their corrosion behaviors in NaCl solutions have been widely reported [22][23][24][25][26][27], no related work about the effect of Cl − concentrations on the corrosion behavior of Mg-Li alloys has been performed.…”
Section: Introductionmentioning
confidence: 99%